NSUN2-mediated RNA m5C modification drives multiple myeloma progression by enhancing the stability of HIP1 mRNA - Yang Jiang; Jing Sun; Yuyan Chen; Lin Cheng; Saran Feng; Yan Wang; Congcong Sun (Scientific Reports)
Abstract RNA 5-methylcytosine (m5C) modification is a crucial epigenetic regulation, and aberrant m5C methylation is associated with the pathogenesis of certain cancers. However, the role and regulatory mechanisms of RNA m5C modification in multiple myeloma (MM) remain unclear. This study aimed to investigate the function and regulatory mechanisms of the primary m5C methyltransferase, NOP2/Sun RNA methyltransferase family member 2 (NSUN2), in MM. The results demonstrated NSUN2 overexpression in patients with MM, and higher NSUN2 levels were associated with poorer outcomes. In addition, elevated global RNA m5C levels were identified in specimens from MM patients, and NSUN2 knockdown decreased RNA m5C levels. Furthermore, NSUN2 knockdown suppressed cell proliferation, promoted apoptosis in vitro, and restrained the progression of xenograft tumors in vivo. Mechanistically, m5C methylated RNA immunoprecipitation (meRIP)-sequencing and RIP-quantitative polymerase chain reaction (RIP-qPCR) assays were applied to screen the candidate targets of NSUN2-mediated m5C modification and huntingtin interacting protein 1 (HIP1) was identified as the target. NSUN2-mediated m5C methylation upregulated HIP1 by enhancing HIP1 mRNA stability. Moreover, HIP1 overexpression counterbalanced the inhibitory effect of NSUN2 knockdown. In conclusion, we propose a novel mechanistic insight into the NSUN2/m5C-HIP1 signaling axis that contributes to the pathogenesis of MM. Thus, NSUN2 can be a novel prognostic biomarker in patients with MM and targeting NSUN2 may be a promising therapeutic strategy.